Increased bone calcium dissociation in lead-exposed rats - Eko Suhartono; Yeni Wahyu Ulfarini; Triawanti Triawanti; Warih Anggoro Mustaqim; Rizky Taufan Firdaus; Muhammad Hafidz Maulana Setiawan (Universa Medicina, 2012)
BACKGROUND Lead is still a major environmental and occupational health hazard, since it is extensively used in the production of paints, gasoline and cosmetics. This causes the metal to be ubiquitous in the environment, being found in the air, soil, and water, from which it can enter the human body by inhalation or ingestion. Absorbed lead is capable of altering the calcium levels in bone. The aim of this study was to demonstrate the effect of lead on bone calcium levels by measuring the reaction constant, Gibbs free energy, and enthalpy. METHODS This study was of pure experimental design using 100 male albino rats (Rattus norvegicus). The experimental animals were assigned by simple randomization to two groups, one group receiving lead acetate orally at a dosage of 100 mg/ kgBW, while the other group did not receive lead acetate. The intervention was given for 4 weeks and the rats were observed weekly for measurement of bone calcium levels by the permanganometric method. RESULTS This study found that k1 (hydroxyapatite dissociation rate constant) was 0.90 x 10-3 dt-1, and that k2 (hydroxyapatite association rate constant) was 6.16 x 10-3 dt-1 for the control group, whereas for the intervention group k1 = 26.20 x 10-3 dt-1 and k2 = 16.75 x 10-3 dt-1. Thermodynamically, the overall reaction was endergonic and endothermic (ΔG > 0 and ΔH > 0). CONCLUSIONS Lead exposure results in increased dissociation rate of bone in comparison with its association rate. Overall, the reaction was endergonic and endothermic (ΔG > 0 and ΔH > 0).